A Model of Religious Value Internalization through Daily Habituation in Early Childhood Character Formation - Siska Perdina; Siti Aisyah; Ratin Wahyu Juni Atma (CV. Yazri Aksara Nusantara, 2026)
The internalization of religious values in early childhood is essential for fostering religious character; however, the processes through which such values become embedded in children's daily behavior remain insufficiently understood. This study aimed to analyze the process of religious value internalization through daily habituation in strengthening early childhood character. A qualitative descriptive approach was employed at TK IT Al-Mumtaz Pontianak, involving three teachers as research participants. Data were collected through observations, semi-structured interviews, and document analysis, and were analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings revealed that religious value internalization develops through three interconnected stages: religious ritual habituation as the value introduction stage, socio-religious habituation as the value cultivation stage, and moral habituation as the character reinforcement stage. These stages collectively facilitate the transformation of religious values from ritual experiences into relatively stable character traits. The study contributes a conceptual model of religious value internalization that highlights the developmental relationship between ritual, social, and moral habituation. The findings provide practical guidance for designing religious character education programs in early childhood settings.Internalisasi nilai religius pada anak usia dini memiliki peran penting dalam pembentukan karakter religius, namun proses bagaimana nilai tersebut berkembang menjadi perilaku sehari-hari masih memerlukan kajian yang lebih mendalam. Penelitian ini bertujuan untuk menganalisis proses internalisasi nilai religius melalui pembiasaan harian dalam memperkuat karakter anak usia dini. Penelitian menggunakan pendekatan deskriptif kualitatif yang dilaksanakan di TK IT Al-Mumtaz Pontianak dengan melibatkan tiga orang guru sebagai partisipan penelitian. Data dikumpulkan melalui observasi, wawancara semi-terstruktur, dan analisis dokumen, kemudian dianalisis menggunakan model interaktif yang meliputi kondensasi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa internalisasi nilai religius berlangsung melalui tiga tahapan yang saling berkaitan, yaitu pembiasaan ritual keagamaan sebagai tahap pengenalan nilai, pembiasaan sosial religius sebagai tahap penanaman nilai, dan pembiasaan moral sebagai tahap penguatan karakter. Ketiga tahapan tersebut membentuk proses yang memungkinkan nilai religius berkembang menjadi karakter yang relatif menetap. Penelitian ini menghasilkan model konseptual internalisasi nilai religius yang dapat digunakan sebagai rujukan dalam pengembangan pendidikan karakter berbasis religius pada anak usia dini.